Power optimization of the ARM7 microprocessor with single-precision floating-point coprocessor - Domingo, Venson John; Navarro, Ian Earl.; Tarroza, Maria Matelle (2008.)
Over the fast few years, the interest in reducing the power consumption of microprocessors has grown rapidly. This is due to the growing popularity of mobile/portable applications that require low power operations to prolong battery-life. Microprocessor designers are compelled to consider power consumption as a major design parameter. Included among the recommendations of the project ?Design and Implementation of ARM7 Microprocessor with Single-Precision Floating-Point Coprocessor? is the power optimization on the coprocessor design. Thus, the objective of this project is to design an analogous system with reduced power consumption. Power optimization included modification on the floating-point architecture class, and the application of Clock-Gating and Control-Signal-Gating on the ARM7 core blocks. A register transfer model of the new design was coded in VHDL and verified using the Cadence® NCLaunch Tool. The design schematic and layout was generated using the Synopsys Design Compiler and Astro tools, and was implemented in standard cells for a 0.25um CMOS process. Aside from power consumption, the final implemented design was characterized in other metrics such as speed and area. Performance was measured using three different metrics namely power, area, and speed. Significant power savings were obtained ranging from 38.04% to 51.86% for the ARM7 core and 27.49% to 31.05% for the Floating-Point Coprocessor for the different testbenches used to characterize the system. The chip area was 2.118770.72 mm². An increase in operational latency was obtained and a maximum allowable frequency of 11.87 MHz was observed. In total the power consumption of the system was reduced from 12.6 mW to 8.47 mW resulting in an average of 33.2% power savings.
Undergraduate Student Project (B.S. CoE)--University of the Philippines, Diliman.
Keywords: RISC microprocessors; Electric power -- Conservation; ARM7 processors; Floating point coprocessors